Photocatalytic material containing regional Lewis acid-base adsorption sites, and preparation and application thereof
By introducing regional Lewis acid-base adsorption sites into the photocatalytic materials, combining anatase-type TiO2, Fe-doped SrTiO3 and Sn-doped SiO2, the problem of insufficient conversion and selectivity in the nitrate reduction process of existing photocatalytic materials is solved, and efficient nitrate reduction to N2 is achieved.
Patent Information
- Application Number
- CN202411617444.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-18
AI Technical Summary
During the photocatalytic reduction of nitrates, existing photocatalytic materials have problems with insufficient nitrate conversion and N2 selectivity, making it difficult to achieve efficient nitrate reduction to N2.
A photocatalytic material consisting of anatase-type TiO2, Fe-doped SrTiO3 and Sn-doped crystalline SiO2 is used to regulate regional Lewis acid-base adsorption sites on the surface of the material to improve the adsorption capacity of NO3− and the reduction intensity of photogenerated electrons.
The efficient nitrate reduction to N2 is achieved, which improves the light absorption performance and catalytic efficiency of the photocatalyst and improves the denitrification efficiency.
Smart Images

Figure CN119633833A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of photocatalytic materials and wastewater treatment, and specifically relates to a photocatalytic material containing regional Lewis acid-base adsorption sites, and its preparation and application. Background Art
[0002] High concentrations of nitrates pose a major threat to the natural environment and human health. It is of practical significance to explore efficient denitrification technologies to reduce nitrates to non-toxic N2. Photocatalytic reduction of nitrates is an important technology to reduce nitrate pollution.
[0003] The photocatalytic reduction of nitrate in water is mainly carried out through two pathways: 1. Indirect reduction process; the photogenerated holes generated in the valence band of the material under light react with the hole scavenger (such as formic acid) to generate CO2 with high reducing ability. − , can react with NO3 in the solution − Reaction; 2. Direct reduction process: The conduction band of the material generates electrons under light, which can react with NO3 adsorbed on the surface of the material. − According to our previous research, the indirect reduction process mainly affects the nitrate conversion rate, while the direct reduction process can affect the nitrate conversion rate and N2 selectivity. The direct reduction process is the key to achieving high nitrate conversion rate and N2 selectivity, and its influencing factors are the material's NO3 − Therefore, it has good photocatalytic activity and NO3 − Photocatalysts with adsorption capacity are a prerequisite for achieving efficient reduction of nitrate to N2.
[0004] The S-type heterojunction formed by the composite of SrTiO3 / TiO2 has been proven to effectively improve the efficiency of carrier migration inside the material. The light scattering material SiO2 can trap scattered light in the lattice to confine light, and increase the light absorption path through forward scattering, thereby improving the photocatalytic performance of the material. In addition, due to the NO3 − It is Lewis alkaline, and the directional adsorption of the material can be controlled by regulating the Lewis acid-base adsorption sites on the material surface. Therefore, SiO2 / SrTiO3 / TiO2 with regulated Lewis acid-base sites is expected to be a potential photocatalytic denitrification material. Summary of the invention
[0005] The present application aims to solve the problems mentioned in the above background technology.
[0006] The present invention discloses a photocatalytic material containing regional Lewis acid-base adsorption sites, wherein the photocatalytic material is composed of anatase TiO2, Fe-doped SrTiO3 and Sn-doped crystalline SiO2, and the chemical formula thereof is Si 1-y Sn y O2 / SrFex Ti 1-x O3 / TiO2.
[0007] In one specific embodiment, the photocatalytic material is SrFe x Ti 1-x Si loaded on the heterojunction formed by O3 and TiO2 1-y Sn y O2, of which Si 1-y Sn y O2 loading is SrFe x Ti 1-x 0.5-5% of O3 / TiO2 mass.
[0008] In one embodiment, the photocatalytic material is SrFe x Ti 1-x There are Lewis acid adsorption sites on the surface of O3. 1-y Sn y There are Lewis base adsorption sites on the O2 surface.
[0009] The present invention discloses a photocatalytic material Si containing regional Lewis acid-base adsorption sites 1-y Sn y O2 / SrFe x Ti 1-x The preparation method of O3 / TiO2 comprises the following steps: S1,SrFe x Ti 1-x Preparation of O3 / TiO2: Anatase TiO2, Sr-containing compound, Fe-containing compound, alkaline compound and deionized water are mixed, stirred for 0.5-1h, added into a hydrothermal kettle, maintained at 160-200°C for 16-30h, and white powder is separated and dried; S2, Sn-SiO2 / SrFe x Ti 1-x Preparation of O3 / TiO2, SrFe x Ti 1-x O3 / TiO2 is mixed with deionized water and a surfactant, stirred at room temperature for 16-24 hours, and then a solid powder is separated and washed with ethanol. The solid powder is then fully mixed with ethanol and deionized water and stirred at room temperature. During the stirring process, tetraethyl silicate and an ethanol solution containing a Sn compound are continuously added at a rate of 6-20 ml / h. After maintaining for 2-2.5 hours, a white powder is separated and washed with ethanol, and then dried in an oven to obtain Sn-SiO2 / SrFe x Ti 1-x O3 / TiO2; S3,Si 1-y Sny O2 / SrFe x Ti 1-x Preparation of O3 / TiO2, Sn-SiO2 / SrFe x Ti 1-x O3 / TiO2 is fully mixed with water and alkaline earth element salt compounds and allowed to stand for 1-5 hours, calcined in an air atmosphere at 800-1000°C for 3-6 hours, and finally the obtained material is soaked in deionized water for 0.5-2 hours, white powder is separated and dried to obtain Si 1-y Sn y O2 / SrFe x Ti 1- x O3 / TiO2.
[0010] In a specific embodiment, in said S1: The Sr-containing compounds are SrCl2, Sr(OH)2 and their corresponding hydrates; The amount of Sr-containing compound is 0.6-1.2 times the molar amount of TiO2; The Fe-containing compounds are FeCl3, Fe(OH)3 and their corresponding hydrates; The amount of Fe-containing compound is 0.02-0.1 times the molar amount of TiO2; The alkaline compound is NaOH or Ca(OH)2; The amount of the alkaline compound used is 1-2 times the molar amount of TiO2.
[0011] In a specific embodiment, in S2: Sn-SiO2 means that the Sn element is doped into the amorphous structure of SiO2; The surfactant is hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride; The amount of surfactant used is SrFe x Ti 1-x 0.5-2 times the mass of O3 / TiO2; The ethanol solution of tetraethyl silicate and the Sn-containing compound is prepared by dissolving tetraethyl silicate and the Sn-containing compound in anhydrous ethanol, wherein the concentration of tetraethyl silicate is 0.025-0.1 mol / L, and the concentration of the Sn-containing compound is 0.001-0.01 mol / L; The Sn-containing compounds are SnCl2, Sn(NO3)2 and their hydrates.
[0012] In a specific embodiment, in S3: Alkaline earth element salt compounds are chlorides, nitrates and hydrates of Ca, Sr and Ba; The amount of alkaline earth element salt compound is Sn-SiO2 / SrFex Ti 1-x O3 / TiO2 molar amount is 0.5-2%.
[0013] The present invention discloses a photocatalytic material Si containing regional Lewis acid-base adsorption sites 1-y Sn y O2 / SrFe x Ti 1-x Applications of O3 / TiO2 include Si 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 photocatalyst is used in photocatalytic denitrification reaction.
[0014] In a specific embodiment, the application includes adding the photocatalytic material, reducing agent and light source as described in any one of claims 1 to 3 to nitrate-containing wastewater, and performing a denitrification reaction by photocatalysis.
[0015] In a specific embodiment, Among them, the Si 1-y Sn y O2 / SrFe x Ti 1-x The dosage of O3 / TiO2 is 0.1‰-0.5‰ of the mass of nitrate wastewater solution; Wherein, the reducing agent is formic acid or oxalic acid, and the dosage is 0mmol / L-60mmol / L; Wherein, the light source is a visible light lamp or an ultraviolet light lamp with a power of 50-500W. Beneficial Effects
[0016] Compared with the prior art, the present application has the following beneficial effects: 1. Combining the SrTiO3 / TiO2S-type heterojunction with high redox ability with the light scattering material SiO2, the resulting material has excellent light absorption performance and high photocatalytic efficiency; 2. Doping Sn with a larger ionic radius into SiO2 makes the local Si-O bonds elongated to form Lewis base sites; doping Fe with an ionic radius similar to Ti into SrTiO3 makes Fe 3+ In-situ substitution of Ti 4+ To achieve electrical neutrality, oxygen vacancies are generated in the material to compensate for the negative charge, thereby introducing Lewis acid sites. − Lewis alkalinity, regional Lewis acid-base sites make NO3 − It is easier to be directionally adsorbed on SrTiO3 to achieve efficient denitrification efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is Si in the present invention 1-y Sn y O2 / SrFe x Ti 1-x SEM image of O3 / TiO2; Figure 2 The NO3 of the simulated nitrate wastewater degraded by the photocatalytic material in Example 2 of the present invention and Comparative Example 1 - Removal situation diagram. DETAILED DESCRIPTION
[0018] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0019] In the description of the present invention, it should be understood that the terms "center", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "counterclockwise", "clockwise", "axial", "radial", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0020] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection, it can be a direct connection, it can be an indirect connection through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. Example 1
[0021] This embodiment provides a photocatalytic material Si containing regional Lewis acid-base adsorption sites. 1-y Sn y O2 / SrFe x Ti 1-x The preparation method of O3 / TiO2 comprises the following steps: S1, 0.5g of anatase TiO2, 1.7g of SrCl2·6H2O, 0.125g of Fe(NO3)3·9H2O, 0.25g of NaOH and 80ml of deionized water were mixed, stirred at room temperature for 1h, added into a 100ml hydrothermal kettle, maintained at 160℃ for 20h, and the white powder was separated and dried; S2, 1g of the material obtained in S1 was mixed with 50ml of deionized water and 1g of hexadecyltrimethylammonium bromide, and stirred at room temperature for 24h, then the solid powder was separated and washed with ethanol, and then the solid powder was fully mixed with 150ml of ethanol and 5ml of deionized water and stirred at room temperature, and tetraethyl silicate and SnCl2·2H2O ethanol solution were continuously added at a rate of 8ml / h during the stirring process, and maintained for 2h, wherein the concentration of tetraethyl silicate was 0.03mol / L, and the concentration of SnCl2·2H2O was 0.002mol / L; then the white powder was separated and washed with ethanol, and finally dried in an oven; S3, 1g of S2 was mixed with 2ml of water and 0.03g of SrCl2·6H2O and allowed to stand for 2h, calcined in an air atmosphere at 850℃ for 4.5h, and finally the obtained material was soaked in deionized water for 1h, the white powder was separated and dried to obtain Si 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2.
[0022] Result analysis: The Si obtained above 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 powder was characterized by SEM. Figure 1 As shown, the material is irregular nanoparticles. Example 2
[0023] This embodiment provides a photocatalytic process for degrading nitrate simulated wastewater.
[0024] Prepare 1L of sodium nitrate simulated wastewater, NO3 - The concentration was 100 mg / L. After ultrasonic mixing with 2 g of the catalytic material obtained in Example 1, the mixture was transferred to a photocatalytic device. 1 ml of formic acid was added. The UV light power was set to 500 W. The total reaction time was 1.5 h. During the process, samples were taken every 15 min and NO3 was tested. - The results are as follows Figure 2 shown. Comparative Example 1
[0025] This comparative example provides a photocatalytic process for degrading nitrate simulated wastewater.
[0026] The photocatalytic process was carried out in accordance with Example 2, except that the catalytic material used was TiO2 (P25). Figure 2 As shown, it is shown that the material obtained in Example 1 has better nitrate reduction ability.
Claims
1. A photocatalytic material containing regional Lewis acid-base adsorption sites, characterized in that: The photocatalytic material is composed of anatase TiO2, Fe-doped SrTiO3 and Sn-doped crystalline SiO2, and its chemical formula is Si 1-y Sn y O2 / SrFe x Ti 1- x O3 / TiO2.
2. A photocatalytic material containing regional Lewis acid-base adsorption sites as claimed in claim 1, characterized in that: The photocatalytic material is SrFe x Ti 1-x Si loaded on the heterojunction formed by O3 and TiO2 1-y Sn y O2, of which Si 1-y Sn y O2 loading is SrFe x Ti 1-x 0.5-5% of O3 / TiO2 mass.
3. A photocatalytic material containing regional Lewis acid-base adsorption sites as claimed in claim 1 or 2, characterized in that: The photocatalytic material is SrFe x Ti 1-x There are Lewis acid adsorption sites on the surface of O3. 1-y Sn y There are Lewis base adsorption sites on the O2 surface.
4. Preparation of a photocatalytic material Si containing regional Lewis acid-base adsorption sites as described in any one of claims 1 to 3 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 method, characterized in that The following steps are involved: S1,SrFe x Ti 1-x Preparation of O3 / TiO2: Anatase TiO2, Sr-containing compound, Fe-containing compound, alkaline compound and deionized water are mixed, stirred for 0.5-1h, added into a hydrothermal kettle, maintained at 160-200°C for 16-30h, and white powder is separated and dried; S2, Sn-SiO2 / SrFe x Ti 1-x Preparation of O3 / TiO2, SrFe x Ti 1-x O3 / TiO2 is mixed with deionized water and a surfactant, stirred at room temperature for 16-24 hours, and then a solid powder is separated and washed with ethanol. The solid powder is then fully mixed with ethanol and deionized water and stirred at room temperature. During the stirring process, tetraethyl silicate and an ethanol solution containing a Sn compound are continuously added at a rate of 6-20 ml / h. After maintaining for 2-2.5 hours, a white powder is separated and washed with ethanol, and then dried in an oven to obtain Sn-SiO2 / SrFe x Ti 1-x O3 / TiO2; S3,Si 1-y Sn y O2 / SrFe x Ti 1-x Preparation of O3 / TiO2, Sn-SiO2 / SrFe x Ti 1-x O3 / TiO2 is fully mixed with water and alkaline earth element salt compounds and allowed to stand for 1-5 hours, calcined in an air atmosphere at 800-1000°C for 3-6 hours, and finally the obtained material is soaked in deionized water for 0.5-2 hours, white powder is separated and dried to obtain Si 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2.
5. The method for preparing a photocatalytic material Si containing regional Lewis acid-base adsorption sites as claimed in claim 4 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 method, characterized in that In S1: The Sr-containing compounds are SrCl2, Sr(OH)2 and their corresponding hydrates; The amount of Sr-containing compound is 0.6-1.2 times the molar amount of TiO2; The Fe-containing compounds are FeCl3, Fe(OH)3 and their corresponding hydrates; The amount of Fe-containing compound is 0.02-0.1 times the molar amount of TiO2; The alkaline compound is NaOH or Ca(OH)2; The amount of the alkaline compound used is 1-2 times the molar amount of TiO2.
6. The method for preparing a photocatalytic material Si containing regional Lewis acid-base adsorption sites as claimed in claim 4 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 method, characterized in that In S2: Sn-SiO2 means that the Sn element is doped into the amorphous structure of SiO2; The surfactant is hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride; The amount of surfactant used is SrFe x Ti 1-x 0.5-2 times the mass of O3 / TiO2; The ethanol solution of tetraethyl silicate and the Sn-containing compound is prepared by dissolving tetraethyl silicate and the Sn-containing compound in anhydrous ethanol, wherein the concentration of tetraethyl silicate is 0.025-0.1 mol / L, and the concentration of the Sn-containing compound is 0.001-0.01 mol / L; The Sn-containing compounds are SnCl2, Sn(NO3)2 and their hydrates.
7. The method for preparing a photocatalytic material Si containing regional Lewis acid-base adsorption sites as claimed in claim 4 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 method, characterized in that In the S3: Alkaline earth element salt compounds are chlorides, nitrates and hydrates of Ca, Sr and Ba; The amount of alkaline earth element salt compound is Sn-SiO2 / SrFe x Ti 1-x O3 / TiO2 molar amount is 0.5-2%.
8. A photocatalytic material Si containing regional Lewis acid-base adsorption sites 1-y Sn y O2 / SrFe x Ti 1-x Applications of O3 / TiO2 include Si 1-y Sn y O2 / SrFe x Ti 1-x O3 / TiO2 photocatalyst is used in photocatalytic denitrification reaction.
9. A photocatalytic material Si containing regional Lewis acid-base adsorption sites as claimed in claim 8 1-y Sn y O2 / SrFe x Ti 1-x The application of O3 / TiO2 is characterized by: The application comprises adding the photocatalytic material, reducing agent and light source as described in any one of claims 1 to 3 to the nitrate-containing wastewater, and performing a denitrification reaction by photocatalysis.
10. A photocatalytic material Si containing regional Lewis acid-base adsorption sites as claimed in claim 9 1-y Sn y O2 / SrFe x Ti 1-x The application of O3 / TiO2 is characterized by: in, The Si 1-y Sn y O2 / SrFe x Ti 1-x The dosage of O3 / TiO2 is 0.1‰-0.5‰ of the mass of nitrate wastewater solution; Wherein, the reducing agent is formic acid or oxalic acid, and the dosage is 0mmol / L-60mmol / L; Wherein, the light source is a visible light lamp or an ultraviolet light lamp with a power of 50-500W.